2016
DOI: 10.1371/journal.ppat.1005715
|View full text |Cite
|
Sign up to set email alerts
|

Metarhizium brunneum Blastospore Pathogenesis in Aedes aegypti Larvae: Attack on Several Fronts Accelerates Mortality

Abstract: Aedes aegypti is the vector of a wide range of diseases (e.g. yellow fever, dengue, Chikungunya and Zika) which impact on over half the world’s population. Entomopathogenic fungi such as Metarhizium anisopliae and Beauveria bassiana have been found to be highly efficacious in killing mosquito larvae but only now are the underlying mechanisms for pathogenesis being elucidated. Recently it was shown that conidia of M. anisopliae caused stress induced mortality in Ae. aegypti larvae, a different mode of pathogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
85
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(110 citation statements)
references
References 60 publications
(53 reference statements)
4
85
0
3
Order By: Relevance
“…Differences in virulence between spore types was first observed in Ae. aegypti infected with conidia or blastospores as reported by Butt et al [13] and Alkhaibari et al [12], respectively. Blastospores attack Ae.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Differences in virulence between spore types was first observed in Ae. aegypti infected with conidia or blastospores as reported by Butt et al [13] and Alkhaibari et al [12], respectively. Blastospores attack Ae.…”
Section: Discussionmentioning
confidence: 88%
“…This novel study demonstrated some of the possible reasons why Culex larvae infected with blastospores take longer to die (LT 50  = 2.68 days) when compared with those exposed to conidia (LT 50  = 1.27 days for wet conidia and 1.45 days for dry conidia). We have recently shown that blastospores of this fungus are highly virulent to A. aegypti larvae, rapidly penetrating the larval integument with the aid of copious amounts of mucilage [12]. Therefore, we were somewhat surprised to find a totally different infection pattern for Culex larvae exposed to M. brunneum [3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations